Criminal Crimes in Elections in Indonesia - Hodijatussolihah; Rosidah; Ahmad Fatoni; Munib; Pipit Yuliarpan; Wiradirja, Hj. Imas Rosidawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
Criminal crimes in elections in Indonesia pose a serious threat to democracy and nation building. Political, social and economic factors are the main drivers, with weak law enforcement exacerbating the situation. Comprehensive efforts from the government, Bawaslu, Gakkumdu, Polri, Prosecutor's Office, community and civil organizations are needed to take action against perpetrators, improve political education and strengthen coordination between institutions. Further research is needed to analyze the modus operandi, actors involved, and the impact of election crimes on democracy